Co‐circulation of alpha‐ and beta‐coronaviruses in Pteropus vampyrus flying foxes from Indonesia. Issue 6 (2nd December 2022) - Ch'ng, Lena; Tsang, Susan M.; Ong, Zoe A.; Low, Dolyce H. W.; Wiantoro, Sigit; Smith, Ina L.; Simmons, Nancy B.; Su, Yvonne C. F.; Lohman, David J.; Smith, Gavin J. D.; Mendenhall, Ian H.
Abstract: Bats are important reservoirs for alpha‐ and beta‐coronaviruses. Coronaviruses (CoV) have been detected in pteropodid bats from several Southeast Asian countries, but little is known about coronaviruses in the Indonesian archipelago in proportion to its mammalian biodiversity. In this study, we screened pooled faecal samples from the Indonesian colonies of Pteropus vampyrus with unbiased next‐generation sequencing. Bat CoVs related to Rousettus leschenaultii CoV HKU9 and Eidolon helvum CoV were detected. The 121 faecal samples were further screened using a conventional hemi‐nested pan‐coronavirus PCR assay. Three positive samples were successfully sequenced, and phylogenetic reconstruction revealed the presence of alpha‐ and beta‐coronaviruses. CoVs belonging to the subgenera Nobecovirus, Decacovirus and Pedacovirus were detected in a single P. vampyrus roost. This study expands current knowledge of coronavirus diversity in Indonesian flying foxes, highlighting the need for longitudinal surveillance of colonies as continuing urbanization and deforestation heighten the risk of spillover events.